INDICATORS OF RENAL MEMBRANOLYSIS IN CHILDREN WITH PYELONEPHRITIS DURING THE COVID-19 PANDEMIC - Gapparova Guli Nurmuminovna; Akhmedjanova Nargiza Ismailovna (Zeta Repository, 2023)
COVID-19 is the biggest challenge facing medicine and scientists in the world in modern times. The highly contagious and severe course of the disease has become a serious test for the global health system.